Efficacy of Chemotherapies and Stem Cell Transplantation for Systemic AL Amyloidosis: A Network Meta-Analysis - Cai, Yuwen; Xu, Shizhang; Li, Na; Li, Song; Xu, Gaosi (Frontiers in Pharmacology, 2020)
Background/aims: The present Bayesian network meta-analysis (NMA) was to compare the efficacy of different chemotherapies and autologous stem cell transplantation (ASCT) in immunoglobulin light-chain (AL) amyloidosis. Methods: We systematically searched PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL) for studies compared the rates of haematological response (HR), complete response (CR), renal response, and cardiac response in AL amyloidosis patients. Results: There were three randomized controlled trials (RCTs) and thirteen observational controlled trials (OCTs) comprising 3402 participants enrolled for the comparisons of 7 treatments: Melphalan + dexamethasone (MDex), high-dose melphalan followed by ASCT, bortezomib + melphalan + dexamethasone (BMDex), thalidomide + cyclophosphamide + dexamethasone (CTD), bortezomib + dexamethasone (BDex), bortezomib + cyclophosphamide + dexamethasone (CyBorD), cyclophosphamide + lenalidomide + dexamethasone (CLD). BMDex was ranked first in the aspect of both HR and CR, CTD induced the highest rate of renal response, and BDex was possibly the best treatment for the cardiac response. Conclusion: Although more data about safety and cost are needed, BMDex was recommended as the most efficient treatment for AL amyloidosis patients for enhancing the response rate for HR and CR. Keywords: amyloidosis, chemotherapy, outcomes research, autologous stem cell transplantation, network meta-analysis